Controversial views on climate change - MAJED, Abu Slemy Lail (One Health & Risk Management, 2021)
Introduction. There have been a lot of discussions in recent years about climate change with an emphasis on global warming. Climate change is a change in the statistical distribution of meteorological patterns when this change lasts over an extended period. Scientists are actively working to understand past and future climate patterns, using theoretical observations and models.The purpose of the research was to understand the direction of climate change towards heating or cooling, in the vision of scientific researchers, in order to develop and implement the action plan for the healthcare system.Material and methods. The research is a descriptive analysis of the controversial views of scientists. To conduct the research, scientific articles were searched on the website of the social scientific network ResearchGate, using the following keywords: climate change, global warming, global cooling, and adaptation. There were selected 5 articles published in 2020.Results. Researchers present controversial evidence regarding climate change. Do controversial opinions focus on the question of climate warming or cooling?Some scientists claim that the planet is threatened by global warming. The United Nations Intergovernmental Panel on Climate Change has estimated that global temperatures will rise by one degree Fahrenheit by 2011 and by 2 degrees Fahrenheit by 2038. The BBC states: „Over the past few hundred years, there has been a steady increase in the numbers of sunspots, at the time when the Earth has been getting warmer. The data suggests solar activity is influencing the global climate causing the world to get warmer." For the last 35 years, the sun has shown a cooling trend. However, global temperatures continue to rise. If the sun's energy decreases as the Earth warms, then the sun cannot be the main temperature control factor. The sun's energy fluctuates over a cycle of about 11 years. The energy changes by about 0.1% on each cycle. If the Earth's temperature were controlled mainly by the sun, then it should have cooled between 2000 and 2008. NASA and climate scientists around the world have said, however, that the years since 1998 have been the warmest in the world.Other scientists say a new ice age awaits us. "An eminent Mexican geophysicist (Victor Manuel Naumovich Velasco Herrera) says that the world may be on the verge of an eighty years cold period similar to the 'little ice age' experienced by Europe from 1300 to 1800 A.D.", a period in which the activity of sunspots decreased significantly.Conclusions. In the Republic of Moldova, there are few studies on the tendencies of climate change towards heating or cooling. The existing ones demonstrate a greenhouse effect both in the short and long term.  Even if all indicators show that global warming is still happening, the idea of global cooling should not be neglected. Whatever the trends, the consequences can be prevented by adapting. Adaptation measures must be carried out at different levels: from the governmental, ministerial to the individual level, as well as from the general within the country to the local level of the administrative system.